A methodical approach to assessing the level of organization of training in the Armed Forces of Ukraine - Heorhadze, Oleksandr; Repilo, Iurii; Kurtseitov, Tymur; Mykus, Serhii; Khoma, Vitalii (Social Development and Security, 2022)
Purpose: To reveal the essence of the methodical approach to assessing the level of organization of training in the Armed Forces of Ukraine. Method: analysis, expert survey. Theoretical value of research: the main results of research on the topic of the article is methodological approach to assessing the level of organization of training in the Armed Forces of Ukraine. Practical value of research: the proposed methodical approach makes it possible to assess the level of organization of training of the defense forces. Value of research: using the specified methodology, subjects of training get the opportunity to make the necessary calculations, provide substantiated proposals to the heads of military organizational structures for making a decision on the organization of training. Type of article: theoretical, practical.